Strategies for Madrasah in Adapting to Educational Digitalization Policies in the Era of Society 5.0 - Sholicha, Syovinatus; Ramdhan, Tobroni (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the strategies employed by MAN 1 Lumajang, an Islamic secondary school in Indonesia, to adapt to the government's educational digitalization policies in the context of Society 5.0. In response to the growing need for digital integration in education, the study investigates how the school has navigated the challenges of limited infrastructure, varying levels of digital literacy among teachers, and unequal access to technology among students. This qualitative case study investigates the strategies employed by MAN 1 Lumajang to adapt to educational digitalization under Society 5.0. Data were collected through semi-structured interviews with school leadership, ICT teachers, and students, classroom observations, and document analysis. Thematic analysis was used to identify key strategies, including digital infrastructure procurement, ongoing teacher training, and the use of platforms like Moodle and Google Classroom. Despite these efforts, challenges such as inconsistent technology access and the need for a more adaptive curriculum remain. The study highlights the importance of strategic planning, teacher professional development, and equitable access to technology in successfully integrating digital tools in Islamic education. The findings offer valuable insights for madrasahs aiming to balance digitalization with Islamic values.